Complete major amputation of the upper extremity: Early results and initial treatment algorithm. Issue 3 (March 2015) - Märdian, Sven; Krapohl, Björn D.; Roffeis, Jana; Disch, Alexander C.; Schaser, Klaus-Dieter; Schwabe, Philipp
Abstract : BACKGROUND: Traumatic major amputations of the upper extremity are devastating injuries. These injuries have a profound impact on patient's quality of life and pose a burden on social economy. The aims of the current study were to report about the initial management of isolated traumatic major upper limb amputation from the time of admission to definitive soft tissue closure and to establish a distinct initial management algorithm. METHODS: We recorded data concerning the initial management of the patient and the amputated body part in the emergency department (ED) (time from admission to the operation, Injury Severity Score [ISS], cold ischemia time from injury to ED, and total cold ischemia time). The duration, amount of surgical procedures, the time to definitive soft tissue coverage, and the choice of flap were part of the documentation. All intraoperative and postoperative complications were recorded. RESULTS: All patients were successfully replanted (time from injury to ED, 59 ± 4 minutes; ISS16; time from admission to operating room 57 ± 10 minutes; total cold ischemia time 203 ± 20 minutes; total number of procedures 7.3 ± 2.5); definitive soft tissue coverage could be achieved 23 ± 14 days after injury. Two thromboembolic complications occurred, which could be treated by embolectomy during revision surgery, and we saw one early infection, which could be successfully managed by serial debridements in our series. CONCLUSION: The management of complete major amputations of the upper extremity should be reserved for large trauma centers with enough resources concerning technical, structural, and personnel infrastructure to meet the demands of surgical reconstruction as well as the postoperative care. Following a distinct treatment algorithm is mandatory to increase the rate of successful major replantations, thus laying the foundation for promising secondary functional reconstructive efforts. LEVEL OF EVIDENCE: Therapeutic study, level V.